Europeanization of Corruption Prevention Policies in Spain - Villoria Mendieta , Manuel; Jiménez Sánchez , Fernando (Revista del CLAD Reforma y Democracia, 2023)
Discussions on how to prevent corruption are now at the heart of the most influential international organizations and research centers. The best ideas in this field are spreading rapidly through all organizations. This fact has combined with the European response to the economic crisis triggered by COVID-19 to generate a new process of change in Spanish anti-corruption policies. The European Union has created the Next Generation Funds (NGEU) to help the member states hardest hit by the pandemic-related crisis not only to recover from it, but also to put in place the necessary reforms to strengthen their resilience to face similar crises in the future. Given that the management of these funds, according to European regulations, is strongly conditioned not only to ensure their effective and efficient use, but also to avoid any risk of corruption, fraud and conflict of interest, all organizations (public and private) that will have any responsibility in the use of this money are obliged to develop solid control schemes that minimize such risks. This fact represents a unique opportunity for the Europeanization and improvement of Spanish anti-corruption policies. This work analyzes, comparatively with previous anti-corruption reforms, the model of change that this reform represents. It also describes the general lines of hard and soft regulation approved on this matter in Spain, as well as the implementation that the ministries most affected by the management of NGEU are carrying out of the control systems promoted by the EU. This work evaluates its positive, but also the negative ones derived from a vertical, abrupt, and accelerated model of change.
Keywords: Administrative Corruption; Ethics; Spain; Europe